Computer visual syndrome: a need to overcome in primary health care - Xiomara Vasallo García; Loreta Sánchez Ortiz; Lisandra Sànchez Peñalver; Vismary Valdés Vales; Estela del Sol Liriano; Ana Home Martìnez (Edumecentro)
Background: technological development and excessive use of electronic devices with screens has led to the appearance of a vision alteration mainly in young people: computer vision syndrome whose early diagnosis would lead to the improvement of the professional performance of graduates in Optometry and Optics of primary health care. Objective: design a system of workshops that contribute to the timely diagnosis of computer visual syndrome in order to improve the professional performance of graduates in Optometry and Optics. Methods: a cross-sectional descriptive study was carried out at the Faculty of Medical Sciences of Cienfuegos in 2022. Theoretical methods were used: historical-logical, analytical-synthetic, inductive-deductive, and modeling; empirical ones: analysis of documents, observation, survey, expert criteria; and mathematic-statistics for the analysis of the data found. Results: the workshop system was designed to improve computer vision syndrome for graduates in Optometry and Optics in primary health care. In its structure it is organized logically and a close relationship is established between the theoretical and methodological components that make it up. Conclusions: the design of a system of workshops with a systemic, contextualized and dynamic nature to overcome computer visual syndrome will allow graduates in Optometry and Optics to make an adequate diagnosis from primary health care.